A Search for Submillimeter Galaxy Counterparts - Blair, Ariana (Proceedings of the Wisconsin Space Conference, 2020)
In this paper, we look to find counterparts to our 450µm sources found in our SCUBA-2 imaging of the Chandra Deep Field – South (CDF-S). We chose sources greater than 4σ and found 21 sources. We then matched the sources to a published 850µm ALMA catalog. We matched the sources within a 4 arcsecond radius and found 12 matches to our 450µm sources. Using the fluxes from the SCUBA-2 CDF-S map and the ALMA 850µm fluxes from the catalog. We created a 450µm to 850µm flux ratio versus redshift plotted against an Arp220 spectral energy distribution (SED) at varying temperatures.